Condensing Osteitis of the Mandible : An Unusual Case Report - Freny Karjodkar; Sunali Khanna (Wolters Kluwer Medknow Publications, 2004)
We describe the symptoms, signs and the appearance of mandibular condensing osteitis in spiral computed tomography based multiplanar and three dimentional reconstruction using computer graphics.